(untitled) (Historia, 2021)
The war at sea between Britain and Spain (1739-48) and Britain and France (1744-48), forming part of the greater Austrian succession struggle, has been seen in Cape history largely in terms of the military defences of the settlement and of the unsuccessful attempt by the British admiral, Edward Boscawen, to reverse French gains in the Indian Ocean region in 1748 with the aid of Dutch auxiliaries. The maritime war, however, affected the Dutch East India Company’s southern African colony in other ways and we select two incidents in these years in order to assess their wider implications.